Salvaging the Unsalvageable: Negative Pressure Wound Therapy for Severe Infection of Prosthetic Breast Reconstruction. Issue 3 (March 2021) - Meybodi, Farid; Sedaghat, Negin; Elder, Elisabeth; French, James; Adams, Kristian; Hsu, Jeremy; Kanesalingam, Kavitha; Brennan, Meagan
Abstract : Background: Severe infections of implant-based breast reconstruction are challenging to treat. Traditional management is removal of the implant with a further attempt at reconstruction months later once the infection has settled. This study evaluates an alternative management protocol using negative pressure wound therapy with instillation (NPWTi). Methods: Consecutive patients with severe peri-prosthetic infection following breast reconstruction were managed using the Implant Salvage Protocol: removal of the prosthesis with application of a NPWTi dressing, changed every 3 days until a negative culture was obtained. A new prosthesis was then placed in the pocket. Data were collected on patient demographics, microbiological, hospital/operative information, and overall success of salvage. Descriptive statistics were used for analysis. Results: In total, 30 breast prostheses in 28 patients were treated for severe peri-prosthetic infection. Twenty-five (83%) implants were salvaged. Mean time from initial reconstruction surgery to presentation was 49.5 days (median 23, range 7–420). Mean hospital stay was 11.5 days (median 12.0, range 6–22), mean number of returns to the operating theater was 3.7 (median 3.0, range 2–7), and mean number of days to negative culture was 5.2 (median 4.0, range 1–14). The most common organisms were methicillin-sensitive Staphylococcus aureus (n = 9) and Serratia marcescens (n = 4). Most had a tissue expander (n = 24, 80%) or implant (n = 5, 16.7%) placed at the completion of therapy. There was no record of capsular contracture nor recurrent infection during follow-up (mean 39.4 months, range 6–74 months). Conclusion: An estimated 83% of prosthetic breast reconstructions with severe infection were successfully salvaged using NPWTi.